Pangenome analysis of Paenibacillus polymyxa strains reveals the existence of multiple and functionally distinct Paenibacillus species - Maggi, Federica (2024)
Paenibacillus polymyxa, a Gram-positive bacterium commonly found in soil and plant roots, plays an important role in the environment due to its nitrogen-fixing ability and is renowned for producing antibiotics like polymyxin. In this study, we present a robust framework for investigating the evolutionary and taxonomic connections of strains belonging to P. polymyxa available at the National Center for Biotechnology Information, as well as five new additional strains isolated at the University of Camerino (Italy), through pangenome analysis. These strains can produce secondary metabolites active against Staphylococcus aureus and Klebsiella pneumoniae. Employing techniques such as digital DNA-DNA hybridization (dDDH), average nucleotide identity (ANI) estimation, OrthoFinder, and ribosomal multilocus sequence typing, we consistently divided these P. polymyxa strains into four clusters, which differ significantly in terms of ANI and dDDH percentages, both considered as reference indices for separating bacterial species. Moreover, the strains of Cluster 2 were re-classified as belonging to the Paenibacillus ottowii species. By comparing the pangenomes, we identified the core genes of each cluster and analyzed them to recognize distinctive features in terms of biosynthetic/metabolic potential. The comparison of pangenomes also allowed us to pinpoint differences between clusters in terms of genetic variability and the percentage of the genome dedicated to core and accessory genes. In conclusion, the data obtained from our analyses of strains belonging to the P. polymyxa species converge toward a necessary reclassification, which will require a fundamental contribution from microbiologists in the near future.